Bona fide gene expression analysis of samples from the bovine reproductive system by microfluidic platform - Fontes, Patricia Kubo [UNESP]; Castilho, Anthony César Souza [UNESP]; Razza, Eduardo Montanari [UNESP]; Nogueira, Marcelo Fábio Gouveia [UNESP] (Elsevier, 2020)
Sample types such as those from reproductive systems often yield scarce material, which limits RT-qPCR analysis to only a few targets. Recently developed high-throughput systems can potentially change this scenario, however, the nanoliter scale of such platforms requires extra processing, e.g., preamplification, which needs to be defined through observation and experience. In order to establish best practices in high-throughput PCR approaches using samples from reproductive systems, we evaluated the Biomark™ HD performance using 11 different sample types from the bovine reproductive system: blastocyst (single/pool), oocyte (pool), cumulus, granulosa, and theca cells, oviduct tissue, fetal ovary, testicle (adult/fetal), and uterine horn. We observed that the preamplification step is not just reliable, but mandatory. Our results indicated that 14-preamplification cycles associated to 5- and 7-fold-dilution is the best approach for those samples. Additionally, the Biomark™ HD system has a high intra and inter reproducibility, therefore its performance in duplicate is unnecessary for the ΔCq analysis, taking in consideration the cutoff value 4 < Cq < 22. In summary, this high-throughput approach is a reliable and excellent tool for studying the bovine reproductive system, especially using quantitatively-limited samples, as a larger number of target genes can be assessed from a very low amount of starting material.
Keywords: Gene expression; High-throughput qPCR system; Low RNA concentration; Microfluids; Preamplification; Reproductive system